2014
DOI: 10.3386/w19920
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mandatory Mortgage Counseling: Can One Dissuade Borrowers from Choosing Risky Mortgages?

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Their results show that simplifying training programs might improve their effectiveness for less sophisticated individuals. In addition, an analysis of a mandatory counseling program for mortgage applicants by Agarwal et al (2015b) found the educational value of the program to be rather limited. Instead, they found that counseling programs that were broad based (based on more than a single financial decision) and longer term were more effective (Agarwal et al, 2010).…”
Section: 31%mentioning
confidence: 97%
See 1 more Smart Citation
“…Their results show that simplifying training programs might improve their effectiveness for less sophisticated individuals. In addition, an analysis of a mandatory counseling program for mortgage applicants by Agarwal et al (2015b) found the educational value of the program to be rather limited. Instead, they found that counseling programs that were broad based (based on more than a single financial decision) and longer term were more effective (Agarwal et al, 2010).…”
Section: 31%mentioning
confidence: 97%
“…Another case is found with mortgage equity withdrawals 6 (Duca and Kumar, 2014); people with a higher financial literacy are less likely to withdraw housing equity. Agarwal et al (2015c) use a dataset from one of the leading subprime lenders in the United States and find that borrowers from the financial industry, who have a higher financial literacy, are less likely to default. Empirical evidence in Taiwan echoes these findings; people with a higher financial literacy are less likely to use highcost credit cards or cash advances (Hsiao et al, 2015b) and are less likely to be overindebted (Shen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, LTV's are less effective in restricting mortgage lending, unless they are allowed to vary over the cycle. Agarwal et al (2014) show that counseling consumers about mortgage risks and alternatives can sometimes be an effective tool to mitigate mortgage risk and show evidence from a US policy experiment that led lower risk mortgage applicants to choose safer mortgage contracts.…”
Section: Policy Optionsmentioning
confidence: 96%
“…Finally, several studies show that predatory lending practices are prevalent and contribute to higher mortgage default rates (Agarwal et al, 2014a), while anti-predatory lending laws and counseling programs improve mortgage outcomes (Bostic et al, 2012;Agarwal et al, 2014b).…”
Section: Rent Extractionmentioning
confidence: 99%